Stone, Paper, Scissors Mini-Game for AI Pet Robot - Aditya Satish Aspat; Elton Lemos; Abhishek Ghoshal (Universitas Sanata Dharma, 2021)
The Artificial Intelligence(AI) Pet Robot is a combination of various fields of computer science. This paper showcases the various functionalities of our AI Pet. Most of the functionalities showcased use the immage processing modules made available through OpenCV. The pet robot has various features such as emotion recognition, follow routine, mini-game etc. This paper discusses the mini-game aspect of the robot. The game has been developed by using VGG16 convolutional network for identification of the action performed by the user. To improve the accuracy we have made use of background subtraction which gives removes all the unwanted objects from the background and gives a simple cutout of the users hand.